2021
DOI: 10.1177/13591045211028169
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 pandemic and obsessive–compulsive disorder in young people: Systematic review

Abstract: Background The COVID-19 pandemic has impacted the world since the first cases were reported in China in January 2020. The secondary mental health impacts of the pandemic are thought to be significant. Obsessive–compulsive disorder is a condition defined by recurrent obsessions and compulsions. It has been hypothesised that the focus on hygiene and contamination during the pandemic could exacerbate obsessive–compulsive symptoms in young people. Method A systematic literature review was conducted. Papers were so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
60
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(66 citation statements)
references
References 14 publications
(44 reference statements)
5
60
0
1
Order By: Relevance
“…Finally, we found that COVID-19 compulsive checking is one of the factors that create stress in people. Extreme focus on hygiene measures and contamination during the COVID-19 pandemic could exacerbate obsessive-compulsive symptoms (Cunning & Hodes, 2022). The COVID-19 pandemic appears to be related with a worsening of obsessive-compulsive symptoms especially during the early stages of the pandemic (Guzick et al, 2021; Maye et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we found that COVID-19 compulsive checking is one of the factors that create stress in people. Extreme focus on hygiene measures and contamination during the COVID-19 pandemic could exacerbate obsessive-compulsive symptoms (Cunning & Hodes, 2022). The COVID-19 pandemic appears to be related with a worsening of obsessive-compulsive symptoms especially during the early stages of the pandemic (Guzick et al, 2021; Maye et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 24 citations met our preliminary criteria and were retained for full-text review. After full-text evaluation, 17 systematic reviews [29,34,[48][49][50][51][52][53][54][40][41][42][43][44][45][46][47], including 6 meta-analytic reviews [34,42,43,46,49,51] met all criteria of this umbrella review and were selected for further analysis (see Table 2).…”
Section: Overview Of the Included Studiesmentioning
confidence: 99%
“…The methodological quality of the reviews was assessed using the JBI critical appraisal checklist (See Supplementary Material). Most of the reviews (n = 13) included in this umbrella review were of high quality [29,34,51,53,54,[40][41][42][43][44][48][49][50], whereas the remaining (n = 4) reviews had medium quality [45][46][47]52]. None of the reviews were identified to have low methodological quality as per the JBI checklist.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…The World Health Organisation (WHO) declared a public health emergency of international concern on 30 January 2020. As of January 2021, there have been over 93,000,000 cases of coronavirus reported to the WHO, including over 2,000,000 deaths [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Anecdotally, some authors have reported increased numbers of patients with obsessivecompulsive disorder (OCD) or personality difficulties seeking psychiatric help in recent months. Predictably, their conditions may be exacerbated by the fear of contagion and of loved ones falling ill or feelings of emptiness when quarantined by others [2,5,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%